PERSONAL DATA PROTECTION IN ISLAMIC FINTECH ECOSYSTEM: TOWARDS A SHARĪʿAH-GOVERNED PRIVACY FRAMEWORK - Abubakar, Ahmad; Sahban, Solauddeen Jibril; Jibreel, Ishaq Sahban (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
This paper examined the ethical and legal imperatives of personal data protection within the context of Islamic fintech, proposing a Sharīʿah-governed privacy framework as a normative response to the digital challenges of the contemporary Islamic financial ecosystem. The paper was premised on the observation that, while Islamic fintech platforms have advanced in providing Sharīʿah-compliant financial products, their data governance practices often lacked a correspondingly rigorous Islamic ethical foundation. Using doctrinal analysis and conceptual clarification, the paper explored foundational Sharīʿah principles of amānah (trust), ḥuqūq al-ʿibād (rights of individuals), maṣlaḥah (public interest), and ḍarar (harm) to assert that personal data constitutes a moral and legal trust whose misuse is a violation of both divine and societal obligations. The paper identified major risks in current Islamic fintech practices, including unauthorised access, algorithmic profiling, unethical monetisation, and limited Sharīʿah oversight in digital operations. It further demonstrated that these risks could not be fully addressed by conventional data protection frameworks such as the General Data Protection Regulations and Nigerian Data Protection Regulations, as these often lacked the theological and ethical depth intrinsic to Sharīʿah. In response, the paper proposed a comprehensive Sharīʿah-compliant data governance model incorporating Digital Sharīʿah Supervisory Boards, Ethical Impact Assessments, and the application of Islamic legal maxims within platform policies. The framework also emphasized user empowerment and cross-jurisdictional harmonisation grounded in Islamic legal epistemology. This paper contributed to the development of an ethically sound, spiritually coherent, and operationally practical model of data protection. It concluded that effective personal data governance in Islamic fintech was not only a technical necessity, but a Sharīʿah obligation aimed at preserving human dignity, justice, and trust in the digital age